ANALISIS PENGARUH AGRESIVITAS PAJAK TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN NON KEUANGAN - Indra Aryudanto; Imam Ghozali (Diponegoro Journal of Accounting, 2016)
The aim of this study is to examine the effect of tax aggressiveness to corporate social responsibility (CSR). Independent variabel used in this study is the tax aggressiveness that measured using proxy of effective tax rates. Dependent variable in this study is the corporate social responsibility (CSR). This study used five control variables, include size, leverage, capint (capital intensity), market to book ratio, ROA.            This study is a replication of the study by Lanis and Richardson (2013) and use 440 non-financial companies that listed on the Indonesian Stock Exchanged in the period 2014 as the sample. Sample were selected by purposive sampling method and finally obtained 440 non financial companies that fulfil the crieteria. Data were analyzed using ordinary least square regression analyysiz model.            This study showed that the aggressiveness of corporate taxes signifacntly and positive related to CSR. Companies that have a high level of tax aggressiveness resulting company would disclose zcSR greater than firm that does tax aggressiveness. This result support the theory of legitimacy